Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
-2 ≠ 2
Step-by-step explanation:
(1 + 3)2 – 10 = 2
(4)2 - 10 = 2
8 - 10 = 2
-2 ≠ 2
Hey there!
“Simplify (1 + 3)2 – 10 = 2”
IN ORDER FOR YOU TO SOLVE FOR THIS EQUATION YOU HAVE TO DO PEMDAS
- (P)arentheses
- (E)xponents
- (M)ultiplication
- (D)ivsion
- (A)ddition
- (S)ubtraction
(1 + 3)2 – 10 = 2
(1 + 3) = 4
4(2) – 10
4(2) = 8
8 – 10 = –2
Answer: –2 ≠ 2 so this makes this statement FALSE
Good luck on your assignment and enjoy your day!
~LoveYourselfFirst:)
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.